Heritability of affectionate communication: A twins study. Issue 4 (1st October 2020) - Floyd, Kory; York, Chance; Ray, Colter D.
ABSTRACT: Using a twin study design, we explored the extent to which affectionate communication is a heritable behavioral trait. Participants ( N = 928) were 464 adult twin pairs (229 monozygotic, 235 dizygotic) who provided data on their affectionate communication behaviors. Through ACE modeling, we determined that approximately 45% of the variance in trait expressed affectionate communication is heritable, whereas 21% of the variance in trait received affection was heritable. A bivariate Cholesky decomposition model also revealed that almost 26% of the covariation in expressed and received affection is attributable to additive genetic factors. These estimates were driven primarily by females and those 50 years of age and older. The results suggest the utility of giving greater attention to genetic and biological influences on communicative behaviors by expanding the scope of communication theory beyond consideration of only environmental influences.